Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Terhadap Hasil Belajar Biologi Pada Materi Keanekaragaman Hayati Di SMA Negeri 1 Batang Hari : The Effect of Application of Cooperative Learning Model Type Teams Games Tournament (TGT) on Biology Learning Outcomes on Biodiversity Materials At the Batang Hari 1 High School - Vinanda Zulfira; Evita Anggereini; Ali Sadikin (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2019)
This study aims to determine the effect of learning Teams Games Tournament (TGT) on the learning outcomes of biology students in class X MIA SMA Negeri 1 Batang Hari. This research is a true experiment with a post-test only control design. The subjects in this study were students of class X MIA SMA Negeri 1 Batang Hari. In the experimental class given the learning treatment with the Teams Games Tournament (TGT) learning model, while in the control class without the Teams Games Tournament (TGT) learning model. To test the difference in the average learning outcomes of the experimental class and the control class on the cognitive aspects, the t-test, normal distributed data, and homogeneous variance were used. From statistical calculations it can be seen that the average value of student learning outcomes in biology class X MIA students in the experimental class has an effect compared to the acquisition of grades in the control class, this is due to the treatment given. In the cognitive aspect that the experimental class (84.90) has an effect compared to the control class (82.35). The average affective aspect, student learning outcomes of the experimental class (85.37) have an effect on the control class (84.68). Based on the t-test on cognitive aspects, it was obtained tcount of 1.87, affective of 1.67. At the 95% confidence level, a table of 2.01 is obtained so that the hypothesis is accepted for both aspects. Based on the results of the study it can be concluded that the effect of the application of the Teams Games Tournament learning model to the learning outcomes of biology students in class X MIA SMA Negeri 1 Batang Hari. Keywords: Cooperative Learning, Model Type Teams Games Tournament (TGT, Biodiversity Materials Abstrak. Peneltian ini bertujuan untuk mengetahui pengaruh pembelajaran Teams Games Tournament (TGT) terhadap hasil belajar biologi siswa kelas X MIA SMA Negeri 1 Batang Hari. Jenis penelitian ini adalah True eksperimen dengan desain post-test only control. Subjek dalam penelitian ini adalah siswa kelas X MIA SMA Negeri 1 Batang Hari. Pada kelas eksperimen diberikan perlakuan pembelajaran dengan model pembelajaran Teams Games Tournamen (TGT), sedangkan pada kelas kontrol tanpa model pembelajaran Teams Games Tournament (TGT). Untuk menguji perbedaan rata-rata hasil belajar kelas eksperimen dan kelas kontrol pada aspek kognitif digunakan uji-t, data terdistribusi normal, dan bervarian homogen. Dari perhitungan statistik dapat dilihat bahwa nilai rata-rata hasil belajar siswa pada mata pelajaran biologi siswa kelas X MIA pada kelas eksperimen berpengaruh dibandingkan dengan perolehan nilai pada kelas kontrol, hal ini disebabkan dari perlakuan yang diberikan. Pada aspek kognitif bahwa kelas eksperimen (84,90) berpengaruh dibandingkan untuk kelas kontrol (82,35). Rata-rata aspek afektif, hasil belajar siswa kelas eksperimen (85,37) berpengaruh dari pada kelas kontrol (84,68). Berdasarkan uji-t pada aspek kognitif diperoleh thitung sebesar 1,87, afektif sebesar 1,67. Pada taraf kepercayaan 95% diperoleh ttabel sebesar 2,01sehingga hipotesis diterima untuk kedua aspek tersebut. Berdasarkan hasil penelitian dapat diambil kesimpulan bahwa pengaruh penerapan model pembelajaran Teams Games Tournament terhadap hasil belajar biologi siswa kelas X MIA SMA Negeri 1 Batang Hari. Kata kunci: Pembelajaran Kooperatif, Teams Games Tournament (TGT), Keanekaragaman hayati